"You Didn't Cause Racism, and You Have to Solve it Anyways": Antiracist Adaptations to Dialectical Behavior Therapy for White Therapists. Issue 4 (November 2022) - Pierson, Ashley M.; Arunagiri, Vinushini; Bond, Debra M.
Highlights: Methods for developing culturally responsive treatment are discussed within a dialectical framework and from the perspective of critical race psychology. We propose that an antiracist adaptation to DBT is needed to correct for context minimization errors in the DBT model that create an invisibility of racism. Recommendations include defining antiracism as a competency domain in therapeutic practice, and amendments and modifications to DBT therapist agreements and tools for treating Black/African-American clients. Abstract: There are currently no published studies that investigate or discuss the cultural responsiveness of Dialectical Behavior Therapy (DBT) to the needs of Black/African-American clients. In addition, no published scholarly works offer guidance to therapists on how to practice antiracism within the context of delivering evidence-based treatment. Methods for developing a culturally responsive antiracist treatment are discussed within a dialectical framework and from the perspective of critical race psychology. We propose that an antiracist adaptation to DBT is needed to correct for context minimization errors in the DBT model that create an invisibility of racism. Recommendations are made for an additional DBT Therapist Agreement that encourages labeling and targeting therapist treatment-interfering racist behavior. An additional Therapist Consultation Agreement is also proposed to guide therapist antiracist advocacy and functional validation for Black/African-American clients. The DBT technology is used in conjunction with other multicultural theoretical models to recommend strategies for developing White DBT therapists' antiracist competencies. Future directions for developing critical race psychological research are discussed.